The Book of Revelation - Cory, Catherine A. (Collegeville, Minn. : Liturgical Press, 2006)
"Complete biblical texts with sound, scholarly based commentary that is written at a pastoral level; the Scripture translation is that of the New American Bible with Revised New Testament and Revised Psalms (1991)"--Provided by publisher.
Rev 1:1-8 : introductory materials -- Rev 1:9-11:19 : first cycle of visions -- Rev 12:1-22:5 : second cycle of visions -- Rev 21:1-22:5 : vision of the New Jerusalem -- Rev 22:6-21 : concluding materials.
Includes index.
Keywords: Bible. -- Commentaries